Non‐coherent adaptive detection in passive radar exploiting polarimetric and frequency diversity. Issue 1 (1st January 2016) - Colone, Fabiola; Lombardo, Pierfrancesco
Abstract : The joint exploitation of polarimetric and frequency diversity is considered in this study as a way to improve the target detection capability in a FM radio‐based passive radar. The authors resort to a generalised likelihood ratio test approach and derive a fully adaptive multi‐frequency polarimetric detector that optimally combines the signals simultaneously transmitted by a given illuminator of opportunity and received at different carrier frequencies by differently polarised surveillance antennas. The application of the proposed detection scheme to recorded live data demonstrates the effectiveness of the multi‐frequency polarimetric operation in typical scenarios, besides the expected improvement due to non‐coherent integration of target echoes received on multiple channels. In particular, it is shown to provide remarkable target discrimination capability against interfering sources as well as increased robustness with respect to the time‐varying characteristics of the exploited signals of opportunity.